The Use of the Structural Analytic Synthetic Method in Arabic Language Learning: Insights from Islamic Elementary Schools in Indonesia - Syadi, Ahmad; suparmanto; Latifah Dayyinati, Erli; Abdan, Nur Sahadah; Khalisah, Salsabila (Journal of Arabic Language Learning and Teaching (JALLT), 2025)
Arabic is an essential international language, particularly in the context of Islam and global communication. This study explores the implementation of the Structural Analytic Synthetic (SAS) method in teaching Arabic reading and writing skills at Madrasah Ibtidaiyah. Using a qualitative approach, data were collected through observation, interviews, and documentation. The findings indicate that the SAS method effectively enhances the reading and writing skills of grade II students at MI NWDI 2 Pancor. Teachers, acting as facilitators, creatively integrate the SAS method with other media, such as pictures and word cards. Despite challenges, particularly in maintaining young students' focus, the gradual application of the SAS method demonstrated positive outcomes. This study contributes significantly to the advancement of Arabic teaching methodologies in Islamic educational institutions in Indonesia.